A Study on the Effect of Consumer Involvement and Affect Intensity before and after Plagiarism Suspicion on the Purchase Intention of Music Goods - Jin-Wan Jo; Mi-Hae Shin; Young-Chul Kim (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This study aims to examine the effect of consumers' involvement and affect intensity on the purchase intention of music items. In particular  domestically, there is no clear standard for judgment of plagiarism, and thus it is expected that plagiarism suspicion is likely to affect consumers' involvement and affect intensity, and as a result, their purchase intention as well. Accordingly, consumer characteristics (involvement, affect intensity) were chosen as independent variables, and consumers' purchase intention on music items as a subordinate variable, respectively. The first questionnaire-based survey was conducted before the awareness of plagiarism suspicion, followed by the second survey after the awareness of plagiarism suspicion. It turned out that the higher level of involvement and affect intensity, both of which are consumer characteristics, the higher level of purchase intention of music goods. While plagiarism suspicion caused C.R values to decrease in every item, a significant difference was observed only in the relation of ‘involvement - purchase intention’. This study shows that music items which involve plagiarism suspicion result in changes in consumers' purchase intention, which will cause damage to the creators and performers of related music items. Thus, for the development of the music industry and creative activity, tools and standards that can clearly distinguish plagiarism need to be developed.